Efektivitas Penggunaan Media E-Booklet Terhadap Pengetahuan dan Sikap Ayah Siaga Tentang Perawatan Kehamilan - Islah Wahyuni (Pusat Penelitian dan Pengabdian Masyarakat (PPPM) STIKes Banyuwangi, 2025)
Ayah Siagas' knowledge and positive attitudes about pregnancy care are essential to support maternal and child health. In short, e-booklets are a very strategic media because they are able to answer the main challenges in the ayah siaga class education due to time constraints, accessibility of information, and the need for practical and interesting materials. This study aims to analyze the effectiveness of using e-booklet media in improving the knowledge and attitudes of ayah siaga regarding pregnancy care in Kualu Village, Kampar Regency. The study was conducted in July 2024, using a quasi-experimental design without a pre-test post-test control group, population of 160 pregnant women and obtained a sample of 31 fathers from the slovin formula to receive educational interventions through e-booklets.. Data were collected using a structured questionnaire to measure knowledge and attitude. Using paired t-test. Results showed a significant increase in knowledge score before and after intervention 0.000 (p<0.05) and attitude before and after intervention 0.000 (p<0.05) in the intervention group. The e-booklet proved to be an effective educational media to increase the capacity of ayah siaga.